TAHAP–TAHAP BIMBINGAN UNTUK MENGATASI KESULITAN BELAJAR - Lydia Ersta Kusumaningtyas & A. Roedy Koesdyantho (Adi Widya : Jurnal Pengabdian Masyarakat, 2018)
The title of this devotion is "Tutoring to overcome learning difficulties" the guidance of learning is part of the guidance and counseling that has the purpose of guiding the child in order to achieve optimum learning achievement (according to his ability), especially for children who have learning difficulties or those whose value is ugly even though the IQ is not low. Parents and teachers are expected to be mentors for children who like it. However, not all parents and teachers can become mentors to children who are having difficulty learning it well. They need to know what they can do to overcome / guide the child in order to perform optimally. To overcome this it is necessary to have additional knowledge and understanding of learning guidance. The target audience in this devotion program is Non-Productive Society of teachers and parents of kindergarten Lakshmi 7 Surakarta. They need to be given additional knowledge because the kindergarten teacher Lakshmi 7 does not have S1 background but Lakshmi 7 kindergarten teacher only from SMK, so the knowledge about guidance and counseling that should be given to the child is not found in school and not understood at all. so also with the parents of students who only average background of high school graduates they also understand the Guidance and Counseling that should be given also for Children. So that both at school and home children do not get guidance as it should be. While the method used in this devotion is Lecture / counseling and discussion and training. In this case, counseling is deemed best suited to increase their knowledge and understanding of counseling and guidance for children. As the evaluation is used questionnaires and discussions to explore their implementation in the field after counseling. The results of this dedication of parents and teachers to understand the importance of tutoring for children overcome learning difficulties. While the results of training as a guide in learning obtained 77.8% (21 Parents and teachers) can carry out its role as a mentor learning for children. So it can be concluded that the implementation of the devotion of learning guidance to overcome learning difficulties in parents and teachers Kindergarten Lakshmi 7 Turisari Surakarta successful. This can be evidenced from the results of the training that was attended by 27 people already able to be a mentor of 21 people.Keywords: Counseling, Guidance learn to overcome learning difficulties, teachers and parents.